Teaching Arabic to Mothers at Islamic Boarding School/ تعليم اللغة العربية للأمهات في المعهد الإسلامي - Riyana, Reni (UIN Raden Mas Said Surakarta, 2020)
Arabic is generally taught in official educational institutions such as schools and institutions under the auspices of the government, the object of learning usually includes the age of school children. There is an institution called Imam Al-Bukhari, which conducts Arabic learning for adults, especially mothers. This study aims to reveal the process of learning Arabic for mothers at the Imam Al-Bukhari Islamic boarding school. This research uses the descriptive qualitative method. Because in this study, the results will be presented in the form of descriptive sentences. Data collection was carried out by interview, observation, and documentation. The data analysis process goes through several stages. including data validation, presenting data, concluding. The result of this research is the method used in learning Arabic level 2 and level 3 is a mixed method. In level 2 learning it was found that mothers had mastered the material during the learning process. Likewise, mothers for level 3 have mastered the learning material provided during the learning process.